A provisional classification of algal-characterised rocky shore biotopes in the Azores. - Tittley, Ian (2000)
Recent studies of the rocky shores of the Azores archipelago have provided information on community structure allowing provisional identification of plant-characterised biotopes (habitats and their associated communities). Although the Azores share some littoral and sublittoral biotopes with the Atlantic coast of mainland Europe. Shores in the archipelago mostly lack the functionally important 'leathery macrophyte' communities of fucoids and laminarians widespread in the North Atlantic. Intertidal biotopes are mainly turfs typical of warm-temperate and tropical regions, and characterised by articulated Corallinaceae or by non-coralline algae such as Cladophora spp., Gelidium spp., Pterocladiella, Stypocaudon scoparia, and Valonia utricularis. Subtidal algal biotopes are characterised by Dictyota spp., Halopteris Filicina, Sphaerococcus coronopifolius and, most commonly, Zonaria tournefortii.